HAKIKAT MANUSIA MENURUT PANDANGAN ISLAM DAN BARAT - Akbar, Ali; Aprison, Wedra; Qadafi, Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2024)
The existence of humans at all times will always be interesting to study, not only limited to philosophy, psychology, or Sufism, the study of humans continues to develop following the growth and development of science. Discussing about human nature will never stop, because there are many interesting dimensions to discuss. Researchers will never completely understand the dimensions of human beings, because before discussing one dimension, another dimension will appear to be discussed. This type of research uses literature review, the purpose of writing is to find out human nature according to Islamic and western views, what is the philosophical view of human nature, how human nature as individuals and members of society tries to describe human nature, its characteristics, potential and the development of its potential. Some philosophers claim that humans are supposed to have tendencies that are believed to be the same as an animal. However, this opinion is contrary to what a Muslim believes. Humans have certain characteristics that are naturally different from animals. They have potential (internal potential or internal tendencies) that can be developed through life experiences or through formal teaching such as schools and other educational institutions. According to Islam humans include two elements, namely physical and spiritual elements. Both are interrelated with each other and then Allah gives potential. in al-the Qur'an is described by al-basyar, al-insan, al-nas, bani adam, and al-Ins. In philosophy, human nature includes spirit, body, combination of spirit and body and their existence. Humans as individual beings are different, because they are influenced by potential. Humans as social beings need other humans. According to the west, human is a potential existence whose manifestation is unpredictable. But that potential is limited. Humans are God's creatures, which may be 'good' or 'bad'. The environment is a determinant of human behavior and behavior is a learned ability.